Preparation method of antibacterial and cell adhesion promoting orthopedic implant

By placing antibacterial agents and bone-promoting peptides in polyphenol compound solutions on the surface of titanium implants, the common bacterial infection and insufficient bone integration problems of titanium implants in clinical applications are solved, and efficient antibacterial properties and win-win results in promoting bone formation are achieved.

CN119857181AActive Publication Date: 2025-04-22BEIJING STOMATOLOGY HOSPITAL CAPITAL MEDICAL UNIV

Patent Information

Application Number
CN202510023497.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-22
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

Titanium implants often face the problems of bacterial infection and insufficient bone integration in clinical applications. The prior art is difficult to achieve excellent antibacterial properties and promote cell adhesion and osteogenesis on a single surface.

Method used

By placing an aqueous solution of polyphenol compounds, polyhexamethyleneguanidine hydrochloride and arginine-glycine-aspartic acid were added, and the titanium tablets were soaked in the solution at room temperature for 12 to 24 hours to prepare an antibacterial-cell adhesion-promoting orthopedic implant.

Benefits of technology

It has achieved efficient bacteria killing on the surface of titanium implants, while promoting the adhesion, proliferation and differentiation of bone marrow mesenchymal stem cells, significantly improving the antibacteriality and osseointegration ability of the implants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857181A_ABST
    Figure CN119857181A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an antibacterial and cell adhesion promoting orthopedic implant, which comprises the following steps: 1) preparing an aqueous solution of a polyphenol compound, adding polyhexamethylene guanidine hydrochloride and arginine-glycine-aspartic acid into the single aqueous solution, and uniformly stirring to obtain a mixture; the mass concentration ratio of the polyhexamethylene guanidine hydrochloride to the arginine-glycine-aspartic acid is (50: 1)-(200: 1); 2) soaking an implant base material in the solution at room temperature to react for 12-24 hours; and (3) after cleaning, obtaining the antibacterial and cell adhesion promoting orthopedic implant. According to the invention, competitive growth of bacteria and cells is realized: cells gt; and growth of bacteria. The win-win situation of resisting bacteria and promoting adhesion and osteogenesis is realized, and the problem of implant loosening caused by infection in orthopedic surgery can be reduced to a certain extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomaterials and relates to a method for preparing an antibacterial and cell adhesion-promoting orthopedic implant. Background Art

[0002] Titanium (Ti) implants have superior physicochemical properties and are favored in orthopedic applications. However, these implants are often faced with challenges of bacterial infection and insufficient bone integration in clinical practice. Implant-associated bone infection is a critical and persistent clinical problem, mainly caused by bacterial colonization and contamination on the implant surface, which may lead to severe inflammation, tissue necrosis, implant loosening, and ultimately implant treatment failure. Infection is mainly attributed to the dominant position of bacteria in the competition for adhesion with tissue cells on the implant surface. Therefore, it is crucial to construct an implant surface that can inhibit bacterial colonization and promote cell adhesion. However, obtaining superior bactericidal properties and satisfactory cytocompatibility is sometimes contradictory, because antibacterial ability is inevitably associated with cytotoxicity. Balancing the antibacterial properties of implant surfaces and the ability to promote osteogenesis is a major challenge. Therefore, developing a strategy that can eliminate bacteria on a single surface while promoting cell attachment and proliferation may provide an effective solution to implant-related problems.

[0003] Various surface functionalization fabrication strategies have been extensively developed, including methods such as anodization, copolymerization, co-immobilization / co-precipitation, layer-by-layer assembly, cross-linking, and loading techniques. Recently, a variety of surface bioactivation strategies have been developed to integrate antimicrobial properties and enhance cell adhesion to promote osteogenic properties on material surfaces. Notable advances include the creation of smart surfaces that evolve during the three phases of the implant life cycle, thereby ensuring long-term antimicrobial resistance, stem cell adhesion, and osteogenic promotion. Carbon dots derived from arginine showed significant bactericidal and osteogenic effects. In addition, implant surfaces treated with copper ion charge conversion coatings showed improved antimicrobial and cell adhesion properties. In addition, biomimetic adaptive nanocomposite arrays provided antimicrobial advantages and stimulated cell proliferation without relying on antibiotics. However, stable modification of bioactive materials usually requires complex, multi-step processes and harsh conditions, such as the use of strong acids or bases and ultraviolet irradiation. Therefore, a universal and facile modification technology is urgently needed to transform material surfaces from bioinert to bioactive.

[0004] To develop a facile bioactivation strategy to create multifunctional surfaces, polyphenol chemistry offers significant advantages by facilitating the attachment of functional components to the surface. In particular, the backbone structure of multiple phenolic hydroxyl groups enables covalent and noncovalent interactions with a variety of biomacromolecules and bioactive ingredients containing -NH2 groups, including the antimicrobial agent polyhexamethyleneguanidine hydrochloride (PHMG) and the osteogenesis-promoting compound arginine-glycine-aspartate (RGD). PHMG is an effective cationic antimicrobial agent that is active against a wide range of microorganisms, including bacteria, viruses, and fungi. In addition, PHMG is stable, cost-effective, and relatively safe for humans and the environment. In addition to its significant bactericidal properties, bioinspired surfaces are also required to promote cell adhesion and osteogenesis. The RGD sequence is present in many extracellular matrix (ECM) proteins, where it can specifically bind to integrins on the cell membrane and, therefore, promote cell adhesion to implants. The integration of RGD peptides is particularly promising, as it has been suggested to accelerate osteogenesis and enhance cell adhesion. However, how to integrate the antimicrobial agent PHMG and the osteogenic enhancing compound RGD onto the implant surface to achieve both antimicrobial and osteogenic properties remains a challenge. Summary of the invention

[0005] In view of this, the present invention provides a method for preparing an antibacterial-cell adhesion-promoting orthopedic implant.

[0006] The present invention specifically provides the following technical solutions:

[0007] A method for preparing an antibacterial-cell adhesion-promoting orthopedic implant, comprising the following steps:

[0008] 1) preparing an aqueous solution of polyphenol compounds, adding polyhexamethyleneguanidine hydrochloride and arginine-glycine-aspartic acid into the mono-aqueous solution, wherein the mass concentration ratio of polyhexamethyleneguanidine hydrochloride to arginine-glycine-aspartic acid is 50:1 to 200:1;

[0009] 2) Soaking the implant substrate in the above solution at room temperature for 12 to 24 hours;

[0010] 3) After cleaning, an antibacterial and cell adhesion-promoting orthopedic implant is obtained.

[0011] Furthermore, the mass concentration ratio of the polyhexamethyleneguanidine hydrochloride to arginine-glycine-aspartic acid is 100:1.

[0012] The concentration of the arginine-glycine-aspartic acid is 100 μg / mL.

[0013] Furthermore, the polyphenol compound is pyrogallol, tea polyphenols or tannic acid.

[0014] Furthermore, the mass concentration ratio of polyhexamethyleneguanidine hydrochloride to arginine-glycine-aspartic acid is 50:1, 100:1, 150:1, and 200:1.

[0015] Furthermore, step 3) is to wash alternately in water and ethanol.

[0016] Furthermore, the implant substrate is a titanium sheet.

[0017] The beneficial effect of the present invention is that while killing bacteria, antibacterial agents often produce similar toxicity to eukaryotic cells, affecting the normal physiological function of cells. While antibacterial agents damage the bacterial cell membrane, the eukaryotic cell membrane will also be destroyed. Since there is a great difference in the size of eukaryotic cells and prokaryotic bacteria, it is very important to regulate the content of antibacterial agents. In addition, antibacterial agents themselves do not have the ability to promote cell proliferation and adhesion. For an orthopedic implant, the ability to promote bone bonding is very important. Therefore, it is very important to deal with bacterial damage under infection conditions and promote cell adhesion growth without affecting cell growth. The present invention obtains the best ratio (100:1) by screening the ratio of different antibacterial / osteoadhesion peptides in the coating. Under this ratio, the coating can achieve a good bactericidal effect (its bactericidal rate reaches 90%), and can significantly promote the adhesion, proliferation and differentiation of bone marrow mesenchymal stem cells (BMSCs). The present invention realizes the competitive growth of bacteria and cells: cell>bacterial growth. A win-win situation of antibacterial and adhesion-promoting bone promotion is achieved, which can reduce the problem of implant loosening caused by infection in orthopedic surgery to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention provides the following drawings:

[0019] Figure 1 This is a diagram of cell-bacteria competitive culture.

[0020] Figure 2 Statistical graph of cell survival rate and antibacterial rate.

[0021] Figure 3 Figure 2 shows cell biocompatibility and cell proliferation promotion.

[0022] Figure 4 Spreading diagram to promote cell adhesion.

[0023] Figure 5 Osteogenic testing for in vivo implantation.

[0024] Figure 6 It is a pull-out experiment to test the bonding force between implant and bone in vivo.

[0025] Figure 7 This is an antibacterial effect diagram. DETAILED DESCRIPTION

[0026] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings.

[0027] Example 1

[0028] The steps of preparing the antibacterial-promoting cell adhesion implant 1 are as follows:

[0029] 1) A polyphenol compound (pyrogallol or tea polyphenols or tannic acid) is dissolved in a buffer solution to prepare a 20 mg / mL tannic acid aqueous solution, and polyhexamethyleneguanidine hydrochloride (PHMG) and arginine-glycine-aspartic acid (RGD) are added to the tannic acid aqueous solution, wherein the concentration of PHMG is 5 mg / mL and the concentration of RGD is 100 μg / mL.

[0030] 2) Soak the titanium sheet in the above solution at 25 degrees for 12 hours;

[0031] 3) The modified titanium sheet was washed alternately in water and ethanol for 5 min.

[0032] The antibacterial-cell adhesion promoting implant obtained in this example is recorded as sample 1.

[0033] Example 2

[0034] The steps of preparing the antibacterial-promoting cell adhesion implant 2 are as follows:

[0035] 1) A polyphenol compound (pyrogallol or tea polyphenols or tannic acid) is dissolved in a buffer solution to prepare a 20 mg / mL tannic acid aqueous solution, and polyhexamethyleneguanidine hydrochloride (PHMG) and arginine-glycine-aspartic acid (RGD) are added to the tannic acid aqueous solution, wherein the concentration of PHMG is 10 mg / mL and the concentration of RGD is 100 μg / mL.

[0036] 2) Immerse titanium sheets of different specifications in the above solution at 25 degrees for 12 hours;

[0037] 3) The modified titanium sheet was washed alternately in water and ethanol for 5 min.

[0038] The antibacterial-cell adhesion promoting implant obtained in this example is recorded as sample 2, also known as Ti-PR.

[0039] Example 3

[0040] The steps of preparing the antibacterial-promoting cell adhesion implant 3 are as follows:

[0041] 1) A polyphenol compound (pyrogallol or tea polyphenols or tannic acid) is dissolved in a buffer solution to prepare a 20 mg / mL tannic acid aqueous solution, and polyhexamethyleneguanidine hydrochloride (PHMG) and arginine-glycine-aspartic acid (RGD) are added to the tannic acid aqueous solution, wherein the concentration of PHMG is 15 mg / mL and the concentration of RGD is 100 μg / mL.

[0042] 2) Immerse titanium sheets of different specifications in the above solution at 25 degrees for 12 hours;

[0043] 3) The modified titanium sheet was washed alternately in water and ethanol for 5 min.

[0044] The antibacterial-cell adhesion promoting implant obtained in this example is recorded as sample 3.

[0045] Example 4

[0046] The steps of preparing the antibacterial-promoting cell adhesion implant 4 are as follows:

[0047] 1) A polyphenol compound (pyrogallol or tea polyphenol or tannic acid) is dissolved in a buffer solution to prepare a 20 mg / mL tannic acid aqueous solution, and polyhexamethyleneguanidine hydrochloride (PHMG) and arginine-glycine-aspartic acid (RGD) are added to the tannic acid aqueous solution, wherein the concentration of PHMG is 20 mg / mL and the concentration of RGD is 100 μg / mL.

[0048] 2) Immerse titanium sheets of different specifications in the above solution at 25 degrees for 12 hours;

[0049] 3) The modified titanium sheet was washed alternately in water and ethanol for 5 min.

[0050] The antibacterial-cell adhesion promoting implant obtained in this example is recorded as sample 4.

[0051] Comparative Example 1

[0052] Pure titanium sheet (Ti) was used as the control group and recorded as sample Ti.

[0053] Comparative Example 2

[0054] Modification of pure titanium with antibacterial agent PHMG: polyphenolic compounds (pyrogallol or tea polyphenols or tannic acid) were dissolved in buffer (pH) to prepare 20 mg / mL tannic acid aqueous solution, polyhexamethylene guanidine hydrochloride (PHMG) was added to the tannic acid solution at a ratio of 15 mg / mL, and the titanium sheet was immersed in the above solution at 25 degrees for 12 hours; the modified titanium sheet was washed alternately in water and ethanol for 5 minutes. It was recorded as sample Ti-P.

[0055] Comparative Example 3

[0056] Modification of pure titanium with cell adhesion promoting peptide RGD: polyphenolic compounds (pyrogallol or tea polyphenols or tannic acid) were dissolved in a buffer solution (pH) to prepare a 20 mg / mL tannic acid aqueous solution, arginine-glycine-aspartic acid (RGD) was added to the tannic acid solution at a ratio of 100 μg / mL, and the titanium sheet was immersed in the above solution at 25 degrees for 12 hours; the modified titanium sheet was washed alternately in water and ethanol for 5 minutes. It was recorded as sample Ti-R.

[0057] Test Example 1 Adhesion-Bactericidal Competition Test

[0058] The cell adhesion and antibacterial properties of the surface of the materials were evaluated. BMSCs and S. aureus and E. coli were inoculated at a ratio of 20:1 (1×10 cells per well and 5×10 cells per 48 wells). 8 CFUs) were inoculated into the control group (pure Ti) and sample 2 (Ti-PR) and incubated for 24 hours. Rinse three times with PBS and fix with 4% PFA for 20 minutes. In order to observe the endocytosis and survival of S.aureus and E.coli by BMSCs, BMSCs and S.aureus, E.coli were labeled with actin 488 (green) and DAPI (blue), respectively. Finally, after rinsing with PBS, CLSM was used to observe the number and morphology of BMSCs and bacteria on the samples.

[0059] Figure 6 This is a cell-bacteria competitive culture diagram. Figure 6 It can be seen that the number of bacteria on the surface of the pure titanium group (Ti) increased significantly, and the morphology of the cells shrank significantly, while the cells on the Ti-PR (sample 2) surface were in good condition and the number of bacteria decreased significantly, which shows that our surface can kill bacteria and promote cell adhesion, and the surface antibacterial-promoting cell adhesion surface was successfully constructed.

[0060] Figure 7 The cell survival rate and antibacterial rate are statistical graphs. Figure 7 It can be seen that by regulating the ratio of different antimicrobial agents and cell adhesion promoting peptides, different materials can be constructed. When the ratio of PHMG:RGD is 200:1, the bactericidal rate reaches more than 90%, but the survival rate is around 70%. By regulating the content of the antimicrobial agent PHMG, the antibacterial activity is maintained at 90% without affecting the antibacterial activity, and the cells have a good survival rate. Through ratio screening, the PHMG:RGD ratio has the best antibacterial and cell adhesion promoting effect when it is 100:1.

[0061] Test Example 2 Adhesion and Proliferation Test

[0062] 1. Cell Culture

[0063] Bone marrow mesenchymal stem cells (BMSCs) were isolated from the femur and tibia of 120 grams of Sprague-Dawley (SD) rats. After the metaphysis was removed, the bone marrow cavity was flushed with MEM-α culture medium (Hyclone, USA) using a syringe. The cells were then collected by centrifugation and cultured in a humidified atmosphere of 37°C and 5% CO2 in a MEM-α culture medium containing 20% ​​fetal bovine serum (FBS) (Hyclone, USA) and 1% penicillin-streptomycin (Hyclone, USA). After 72 hours of culture, BMSCs were passaged and the culture medium was replaced with a MEM-α culture medium containing 10% FBS and 1% penicillin-streptomycin. The following experiments were performed using the 4th generation BMSCs.

[0064] 2. Cytocompatibility test

[0065] To test the biocompatibility, sterile Ti, Ti-P, Ti-R and Ti-PR (sample 2) were placed in a 48-well plate with three parallel samples in each group. 25,000 BMSCs were inoculated in each sample and cultured for 24 hours. Then, 10 mg of MTT was weighed and dissolved with 1 mL of PBS, and then 9 mL of pure culture solution was added for dilution, and 100 μL of MTT solution was added. The well plate was placed in an incubator for 4 hours, the remaining culture solution in the well plate was absorbed, and 100 μL of DMSO was added to each well and shaken thoroughly. 100 μL of solution was taken from each well and measured at a wavelength of 490 nm using a microplate reader (Thermo Fisher, 51119200, USA). Afterwards, the survival rate of BMSCs was calculated and the biocompatibility of each group was evaluated.

[0066] Cell counting kit-8 (CCK-8, Sigma-Aldrich) was used to evaluate the proliferative effect of titanium surface on BMSCs. The samples were placed in a 48-well plate and inoculated with 200 μL of BMSCs cell suspension at a density of 1.0×10 cells per well. After culturing titanium sheets with BMSCs for 1, 4, and 7 days, the samples were transferred to a new 48-well plate, 200 μL of CCK-8 solution was added, and incubated at 37°C for 3 hours. Finally, 100 μL of CCK-8 solution was taken out, and the absorbance (OD) was measured at a wavelength of 450 nm using a microplate reader (Thermo Fisher, 51119200, USA) to evaluate the proliferative effect of titanium surface on cells.

[0067] Figure 1 Figure 2 shows cell biocompatibility and cell proliferation promotion.

[0068] from Figure 1 As can be seen in (left), the cell survival rate of the Ti-PR group (sample 2) is above 80%, which shows good biocompatibility.

[0069] from Figure 1 (Right) It can be seen that after 1 day, 4 days and 7 days of co-culture of cells on the titanium surface, the Ti-PR group (sample 2) surface promoted cell proliferation. This is mainly because the RGD structure and phenolic hydroxyl structure on the surface of sample 2 coating promoted cell proliferation.

[0070] 3. Cell Adhesion

[0071] A 1 × 1 cm titanium plate was used to observe cell adhesion in each group. BMSCs were plated at 5 × 10 per cm2. 3 The cells were seeded at a density of 10 cells per sample in a 48-well plate. After 48 hours of cell culture, they were fixed with 4% formaldehyde (PFA, Biosharp, BL539A, China) for 20 minutes and permeabilized with 0.1% (v / v) Triton-X 100 (Sigma, 9002-93-1, USA) for 3 minutes. After rinsing twice with PBS, they were blocked with 1% (w / v) bovine serum albumin (BSA, Sigma, B2064, USA) solution in PBS for 30 minutes, and then treated with 0.165 μmol L-1 of rhodamine phalloidin (Invitrogen, R415, USA) and 4,6-diamino-2-phenylindole (DAPI, Invitrogen, D1306, USA) in the dark for 20 minutes to visualize filamentous actin (F-actin) and cell nuclei, respectively. After rinsing with PBS, BMSCs on the samples were observed using CLSM. BMSCs were seeded on each sample of a 48-well plate, cultured for 48 hours, and then fixed with 4% PFA. After rinsing twice with PBS, the cells were dehydrated with gradient concentrations of ethanol (10%, 20%, 30%, 40%, 60%, 70%, 80%, 90%, 100%), followed by critical point drying and platinum plating. The morphology of the cells on the samples was observed using SEM.

[0072] Figure 2 This is a spreading diagram to promote cell adhesion. Figure 2 It can be seen from the spreading and adhesion effect of BMSC cells on the surfaces of different materials that compared with pure titanium (Ti), the cell surface spreading area of ​​Ti-PR (sample 2) is larger, and the SEM test surface has similar results. The good cell spreading adhesion is mainly because PHMG does not affect cell activity while RGD promotes cell adhesion and spreading.

[0073] Test Example 3 In vivo implantation osteogenic test

[0074] 1. In vivo micro-computed tomography analysis of peri-implant bone tissue morphology

[0075] Male SD rats weighing about 280g were selected for femoral implantation experiments to evaluate the in vivo anti-infection and osteogenic properties of the materials. The modeling method is as follows: After the anesthesia is effective after intraperitoneal injection of 10% chloral hydrate, the right femur of each rat is taken, the skin is prepared, and a titanium column with a diameter of 1mm and a length of 2.mm is implanted on the proximal side of the metaphysis near the knee joint. According to the surface modification of the titanium column, it is divided into two groups: the control group: the pure titanium surface is not modified, and the experimental group: Ti-PR (sample 2). After implantation, the skin is pulled and sutured. At 4 weeks, 8 weeks and 12 weeks after surgery, the rats were euthanized, and the femurs containing implants were collected and fixed with 10% neutral buffered formaldehyde for 48 hours. In order to evaluate the new bone tissue around the implant, the femurs containing implants were scanned using a micro-computed tomography system (SkyScan1276 scanner, USA). The scanning protocol was set to a voltage of 85kV, a current of 130μA and a resolution of 9.00μm. New bone formation around the implants was evaluated in a volume of interest (VOI) based on a hollow cylindrical area with a radius of 200 μm from the implant surface. In addition, quantitative analysis of micro-computed tomography, including bone volume fraction (bone volume / total volume, BV / TV), trabecular thickness (Tb.Th), trabecular number (Tb.N), and trabecular separation (Tb.Sp), was performed. In addition, three-dimensional (3D) reconstruction of each sample was performed using Mimics Medical 21.0 software (Materialise, Belgium) to visualize new bone formation around the implants.

[0076] Figure 3 Micro-CT cross-sectional images and 3D reconstruction images of peri-implant bone tissue and bone tissue morphometric analysis results of the region of interest, including bone volume / total volume (BV / TV), trabecular thickness (Tb.Th), trabecular number (Tb.N) and trabecular separation (Tb.Sp). Figure 3It can be seen that in the early stage of healing for 4 weeks, the Ti-PR group (sample 2) showed better peri-implant osteogenesis, which continued to rise at 8 weeks until it reached the highest after 12 weeks. The implant surface was covered with a large amount of new bone tissue, while only a small part of the new bone was formed on the Ti surface of the control group. Compared with the Ti group, the BV / TV values ​​of the Ti-PR group (sample 2) were significantly higher at 4 weeks, 8 weeks and 12 weeks. Similarly, the Ti-PR (sample 2) group also showed better Tb.Th, Tb.N and Tb.Sp values ​​than the Ti group. These results show that the implant of the present invention can promote higher quality and larger amounts of new bone formation compared with the Ti implant. Taking into account the time dimension, the implant of the present invention shows enhanced bone integration ability over time compared with the Ti implant, indicating that the modified surface of the present invention not only has superior early bone formation ability, but also has long-term bone regeneration ability. It is shown that the good bone integration performance of the implant of the present invention is largely due to its excellent anti-infection properties. The results show that the material of the present invention can significantly promote peri-implant osteogenesis.

[0077] 2. In vivo biomechanical testing

[0078] The animal modeling method was the same as above, and the biomechanical pull-out test of the implant bone integration strength was performed to quantify the bone integration strength between bone tissue and implant. At 4 weeks, 8 weeks and 12 weeks after surgery, the rats were euthanized, and the right femur containing the implant was collected and fixed with 10% neutral buffered formaldehyde for 48 hours. A custom three-valve collar was connected, which could clamp the implant and was connected to a universal testing machine (EZ-LX 50N, Shimadzu Instrument Co., LTD). An axial tensile force was applied to the implant at a rate of 5.0 mm min-1, and the pull-out force was recorded by the universal testing machine (the pull-out force was defined as the maximum value of the load-displacement curve).

[0079] To evaluate the bonding strength of the implants, biomechanical testing was performed by recording the maximum pull-out force of the implants. Figure 4 The three-piece chuck is used to pull out the titanium column from the femoral tissue. Figure 4 It can be seen from the figure that compared with the Ti group, the pull-out force of the Ti-PR (sample 2) group after 4, 8 and 12 weeks of implantation was 50.9%, 34% and 24% higher than that of the control group, respectively, indicating that the implant of the present invention has better bone integration ability, thereby increasing the long-term stability of the bone implant.

[0080] Test Example 4 Sterilization Test

[0081] The antibacterial properties of samples Ti, Ti-P, Ti-R and Ti-PR (sample 2) were tested by film pasting, surface dead and alive staining, and bacterial scanning electron microscopy observation.

[0082] (1) Film adhesion method: The antibacterial properties of the samples were tested using the film adhesion method (QB / T2591-2003). The samples were cut into 2 cm × 2 cm square pieces and sterilized under ultraviolet light for 2 hours before being placed in a 6-well plate. 32 μL of Staphylococcus aureus or Escherichia coli suspension (2 × 10 5 CFU mL-1), incubated at 37°C for 24 hours. Then, the sample was transferred to a 15 mL centrifuge tube containing 4 mL of sterile PBS and vortexed for 30 seconds to separate the bacteria from the sample surface. Next, the obtained bacterial suspension was diluted at a ratio of 1:200, and 50 μL of the diluted bacterial suspension was spread on a standard agar plate and incubated at 37°C for 24 hours. The number of bacteria on the surface was evaluated by counting the colonies on the agar plate. The inhibition efficiency (η) was determined by formula (1):

[0083] η=[(A0-A1) / A0]×100% (1)

[0084] Among them, A1 is the colony count value of the culture dish containing the titanium surface, and A0 is the blank positive control.

[0085] (2) Surface live or dead staining: The samples were sterilized under ultraviolet light at room temperature for 2 hours and then placed in a 48-well plate. 200 μL of bacterial suspension (Staphylococcus aureus or Escherichia coli, 10 8 CFU mL-1), after incubation at 37°C for 12 hours, the sample was removed from the 48-well plate, rinsed 3 times with sterile PBS and placed on a slide. Pre-mix 1 mL of DMAO and 2 mL of EthD-III in the live and dead bacteria staining kit in a microcentrifuge tube, add 8 mL of 0.85% NaCl solution after thorough mixing to obtain a 100× dye solution, and then dilute the dye solution to 1× with LB liquid culture medium. 200 μL of dye solution was added to the sample surface and incubated in the dark at room temperature for 15 minutes, then rinsed 3 times with sterile PBS. Observe by CLSM using a 63× oil immersion lens. Live (green fluorescence) and dead (red fluorescence) bacteria can be observed using FITC and Cy3 (or TexasRed) channels, respectively.

[0086] (3) Bacterial scanning electron microscopy observation: To evaluate the antibacterial effect, the morphology of bacteria was studied. A 1×1 cm titanium sheet was used. 200 μl of bacterial suspension (Staphylococcus aureus or Escherichia coli, concentration 10 8CFU / mL), cultured at 37°C for 12 hours, and then fixed with 2.5% glutaraldehyde (Sigma-Aldrich, G6257, USA) at 4°C for 12 hours. After two PBS rinses, the samples were dehydrated with gradient concentrations of ethanol (10%, 20%, 30%, 40%, 60%, 70%, 80%, 90%, 100%), followed by critical point drying and platinum sputtering (Leica, EM CPD300, Germany). The morphology of bacteria on the samples was observed by scanning electron microscopy (SEM).

[0087] Figure 5 The results of colony culture, bacterial scanning electron microscopy and live-death staining are shown below. Figure 5 It can be seen that the number of bacteria on the surface of Ti, Ti-P, Ti-R and Ti-PR (sample 2) is significantly reduced, and the antibacterial rate can reach more than 99%. At the same time, this is proved by the live and dead staining of bacteria. The number of dead bacteria on the surface is significantly increased. The antibacterial properties of the surfaces of Ti, Ti-P, Ti-R and Ti-PR (sample 2) are not affected, and have an antibacterial rate of more than 99%. They have excellent killing effects on different positive and negative bacteria. It can be seen from the SEM image that the bacteria on the surface of Ti-P and Ti-PR are obviously wrinkled, and the bacterial cell membrane is obviously damaged. This is mainly due to the presence of PHMG on the surface. Its guanidine group destroys the bacterial cell membrane, which further shows that the coating has excellent antibacterial properties.

[0088] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A method for preparing an antibacterial-cell adhesion-promoting orthopedic implant, characterized in that: Here are the steps: 1) preparing an aqueous solution of polyphenol compounds, adding polyhexamethyleneguanidine hydrochloride and arginine-glycine-aspartic acid into the mono-aqueous solution, wherein the mass concentration ratio of polyhexamethyleneguanidine hydrochloride to arginine-glycine-aspartic acid is 50:1 to 200:1; 2) Soaking the implant substrate in the above solution at room temperature for 12 to 24 hours; 3) After cleaning, an antibacterial and cell adhesion-promoting orthopedic implant is obtained.

2. The method for preparing an antibacterial-cell adhesion-promoting orthopedic implant according to claim 1, characterized in that: The mass concentration ratio of polyhexamethyleneguanidine hydrochloride to arginine-glycine-aspartic acid is 100:

1.

3. The method for preparing an antibacterial-cell adhesion-promoting orthopedic implant according to claim 1, characterized in that: The concentration of the arginine-glycine-aspartic acid is 100 μg / mL.

4. The method for preparing an antibacterial-cell adhesion-promoting orthopedic implant according to claim 1, characterized in that: The polyphenol compound is pyrogallol, tea polyphenol or tannic acid.

5. The method for preparing an antibacterial-cell adhesion-promoting orthopedic implant according to claim 1, characterized in that: The mass concentration ratio of polyhexamethyleneguanidine hydrochloride to arginine-glycine-aspartic acid is 50:1, 100:1, 150:1, and 200:

1.

6. The method for preparing an antibacterial-cell adhesion-promoting orthopedic implant according to claim 1, characterized in that: Step 3) is to wash alternately in water and ethanol.

7. The method for preparing an antibacterial-cell adhesion-promoting orthopedic implant according to claim 1, characterized in that: The implant substrate is a titanium sheet.

Citation Information

Patent Citations

  • Application of coating based on hyaluronic acid-RGD polypeptide in preparation of medical material for promoting osteoblast repair and macrophage inflammation regulation

    CN118286524A

  • Anti-microbial medical implants and uses thereof

    US20060121083A1

Cited By

  • Rapid detection kit based on confocal microorganism and cell multi-fluorescence labeling and preparation method of rapid detection kit

    CN120253795A